The Concept of Fitrah and the Implications of Islamic Education - Iffatul Hanief; Siti Jahro Sawaliyah; Mahwiyah (Amandemen: Journal of Learning, Teaching and Educational Studies, 2023)
Islamic education is a process of instilling divine values that are formulated systematically and adaptively, which are adapted to the abilities and potential development of students. So the pattern of education offered must be adapted to the physical and psychological needs of students as educational subjects. If not, the educational process offered will experience obstacles. For this reason, the education carried out must be able to touch all human aspects as a whole, namely the physical and spiritual aspects. In the perspective of Islamic Education, it can be seen that human nature is a creature that is completely limited and requires efforts to make its presence on this earth more perfect, so efforts are needed. The effort is through education. Therefore, the distinctive nature of Islamic education is to try to develop the characteristics and potential of its students effectively and dynamically.